Ozonolysis pre-treatment of waste activated sludge for solubilization and biodegradability enhancement - Otieno, Benton; Apollo, Seth; Kabuba, John; Naidoo, Bobby; Simate, Geoffrey; Ochieng, Aoyi (Journal of environmental chemical engineering, 2019)
Handling of waste activated sludge (WAS) has been a great problem due to its low biodegradability which is contributed by the biorecalcitrant bacterial cells from the activated sludge process. Moreover, the sludge is poorly soluble which makes it difficult to subject to a further biological treatment downstream. This study investigated the application of ozonolysis pre-treatment for the solubilization and biodegradability enhancement of municipal WAS. Ozonolysis led to sludge solubilization as was shown by a 50% reduction in total suspended solids (TSS). Subsequently, the dissolved organic carbon (DOC) increased by 25%, and sludge biodegradability increased two-folds. The mechanism of sludge solubilization was explained through cell content analysis which revealed biomass cell wall rapture during ozonolysis leading to the release of the cellular contents including humic substances, proteins, phosphates, nitrates and carbohydrates into the supernatant. The soluble proteins decreased by 98% while carbohydrates increased four-fold. Additionally, sulphates in the supernatant increased from 18 mg/L to 45 mg/L while nitrates increased from 0 mg/L to 85 mg/L indicating oxidation of the organic nitrogen and phosphorus which are constituents of the biomass cell protein; this can provide nutrient balance in the downstream biological treatment method. Thermogravimetric (TGA) analysis showed that the weight loss for ozone-treated WAS was 10% while that for the raw WAS was 20% further indicating that ozonolysis had solubilized the volatile and organic components of the treated WAS. Ozonolysis is a promising technology for the pre-treatment of WAS before anaerobic digestion for stabilization and energy recovery.